Strategies in translating proper names from English into Vietnamese in fantasy literature: A case study in Book I of the Game of Thrones series = Chiến lược dịch Anh – Việt tên riêng trong văn học kỳ ảo: Nghiên cứu trường hợp tập 1 Trò chơi vương quyền - Nguyễn, Hồng Linh (2020)
This study aims to identify strategies employed in translating proper names in Book I of the Game of Thrones series as well as to propose helpful implications in English-Vietnamese translation of proper names in fantasy. Document analysis and personal interview are the two main research instruments adopted in the study. Based on the framework by Fernandes (2006), the thesis has determined translation strategies of proper names in the selected case, namely Rendition, Copy, Substitution, Recreation, Deletion, Addition, and Transposition. Several translation patterns and tendencies were also presented for each group of proper names. It is hoped that this study will be beneficial for students and translators dealing with the translation of proper names, particularly those in fantasy literature.